Automated observatory in Antarctica: real-time data transfer on constrained networks in practice - S. Bracke; A. Gonsette; J. Rasson; A. Poncelet; O. Hendrickx (Geoscientific Instrumentation, Methods and Data Systems, 2017)
In 2013 a project was started by the geophysical centre in Dourbes to install a fully automated magnetic observatory in Antarctica. This isolated place comes with specific requirements: unmanned station during 6 months, low temperatures with extreme values down to −50 °C, minimum power consumption and satellite bandwidth limited to 56 Kbit s−1. The ultimate aim is to transfer real-time magnetic data every second: vector data from a LEMI-25 vector magnetometer, absolute F measurements from a GEM Systems scalar proton magnetometer and absolute magnetic inclination–declination (DI) measurements (five times a day) with an automated DI-fluxgate magnetometer. Traditional file transfer protocols (for instance File Transfer Protocol (FTP), email, rsync) show severe limitations when it comes to real-time capability. After evaluation of pro and cons of the available real-time Internet of things (IoT) protocols and seismic software solutions, we chose to use Message Queuing Telemetry Transport (MQTT) and receive the 1 s data with a negligible latency cost and no loss of data. Each individual instrument sends the magnetic data immediately after capturing, and the data arrive approximately 300 ms after being sent, which corresponds with the normal satellite latency.